Keadilan Pancasila dalam Persepektif Teori Keadilan Aristoteles - Riky Sembiring (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2018)
The basis of Pancasila justice is found in points 2 and 5, which reads the second principle of just and civilized humanity and the fourth principle of justice for all Indonesian people. Fair and civilized human values, that awareness of attitudes and behaviors that are in accordance with moral values ​​in living together on the basis of the demands of conscience by treating things as they should. Humans need to be treated according to their dignity and dignity, as God's creatures who are equal and have the same rights and human obligations. Based on this value, there is absolutely recognition of human rights. The value of social justice for all Indonesians implies both the basis and the goal, namely the achievement of a just and prosperous Indonesian society both physically and mentally. Based on this value, justice is a very basic value that is expected by all nations. The expected Indonesian state is an Indonesian state that is just. Justice is described fundamentally by Aristotle, namely to know about justice and injustice, three main things must be discussed, namely what actions are associated with the term, what justice means, and between the two extreme points whether justice lies.